Is corpus word frequency a good yardstick for selecting words to teach? Threshold levels for vocabulary selection. (July 2015) - Okamoto, Mayumi
Abstract: This paper examines the suitability of word frequency as a criterion for vocabulary selection in general courses of English as a Foreign Language. Specifically, it addresses two issues: the relation between word frequency in corpora and native speakers' self-reported frequency of word use, and the relation between word frequency and word dispersion in corpora. Seventeen native speakers of English were asked how frequently they think they use 240 target words. The dispersion rates of the target words were calculated according to their sub-frequencies observed in the British National Corpus and the Corpus of Contemporary American English. The results indicate that corpus word frequency is closely related to native speakers' self-reported frequency of word use up to the 7000-word level, and that word frequency is related to word dispersion, with high dispersion rates observed up to the 6000-word level. These results have important implications for vocabulary selection for EFL textbooks and goal setting for vocabulary teaching. They suggest that native speakers make reasonable judgments on word usefulness up to the 7000-word level in terms of frequency. Furthermore, it would seem sensible to set the upper limit of vocabulary teaching at the 6000-word level in terms of frequency and dispersion.